Metabolic alterations precede neurofilament changes in presymptomatic ALS gene carriers - Dorst, Johannes; Weydt, Patrick; Brenner, David; Witzel, Simon; Kandler, Katharina; Huss, André; Herrmann, Christine; Wiesenfarth, Maximilian; Knehr, Antje; Günther, Kornelia; Müller, Kathrin; Weishaupt, Jochen H.; et al. (EBioMedicine, 2023)
Background - The emergence of potentially effective new therapies for genetic forms of amyotrophic lateral sclerosis (ALS) necessitates the identification of biomarkers to facilitate early treatment, prior to the onset of motor symptoms. Here, we sought to investigate whether metabolic alterations are detectable in presymptomatic ALS gene mutation carriers, and whether such alterations precede neurofilament light chain (NfL) changes in serum. - Methods - Between 02/2014 and 11/2021, we prospectively studied 60 presymptomatic ALS gene mutation carriers (40% male, age 48.7 ± 14.9; 28 C9orf72, 22 SOD1, 10 other) compared to 73 individuals from the same families (47% male, age 47.4 ± 12.9) without pathogenic mutations as controls. Bioimpedance analysis (BIA) and indirect calorimetry were performed, and Body Mass Index (BMI), Fat Mass (FM), Body Fat Percentage, Body Water (BW), Lean Body Mass (LBM), Extracellular Mass (ECM), Body Cell Mass (BCM), ECM/BCM ratio, Cells Percentage, Phase Angle, Resting Metabolic Rate (RMR), Metabolic Ratio (MR), and NfL were measured. Participants and evaluators were blinded regarding gene carrier status. - Findings - Presymptomatic ALS gene carriers showed reduced LBM (p = 0.02), BCM (p = 0.004), Cells Percentage (p = 0.04), BW (p = 0.02), Phase Angle (p = 0.04), and increased ECM/BCM ratio (p = 0.04), consistently indicating a loss of metabolically active body cells. While in C9orf72 mutation carriers all tissue masses were reduced, only metabolically active tissue was affected in SOD1 mutation carriers. Unexpectedly, RMR (p = 0.009) and MR (p = 0.01) were lower in presymptomatic ALS gene carriers compared to non-carriers. NfL serum levels were similar in mutation carriers and non-carriers (p = 0.60). - Interpretation - The observed metabolic phenomena might reflect reduced physical activity and/or preemptive, insufficient compensatory mechanisms to prepare for the later hypermetabolic state. As pre-symptomatic biomarkers we propose ECM/BCM ratio and Phase Angle for SOD1, and a 4-compartment affection in BIA for C9orf72 mutation carriers. - Funding - This work was an investigator-initiated trial. On the German side, there was no institutional or industrial funding. On the Swedish side, this work was supported by grants from the Swedish Brain Foundation (grants nr. 2013-0279, 2016-0303, 2018-0310, 2020-0353), the Swedish Research Council (grants nr. 2012-3167, 2017-03100), the Knut and Alice Wallenberg Foundation (grants nr. 2012.0091, 2014.0305, 2020.0232), the Ulla-Carin Lindquist Foundation, Umeå University (223-2808-12, 223-1881-13, 2.1.12-1605-14) and the Västerbotten County Council (grants nr 56103-7002829), King Gustaf V:s and Queen Victoria's Freemason's Foundation.
Online verfügbar: 12. März 2023, Artikelversion: 12. März 2023
Gesehen am 20.03.2024